THE ROLE OF ARTIFICIAL INTELLIGENCE IN SHAPING PERSONAL COMMUNICATION CULTURE - Normatov Sanjar Abdug’ani o’g’li (Uzbekistan Open Conference, 2026)
This article provides a scientific and theoretical analysis of the impact of artificial intelligence on personal communication culture. Along with the positive effects of artificial intelligence on communication culture, the potential negative consequences arising from its excessive use are also examined. The necessity of fostering a culture of conscious and purposeful use of AI technology — treating it not as a force that replaces human potential, but as a tool that expands human capabilities — and teaching its proper application on this basis is substantiated.
Keywords: artificial intelligence; communication culture; intellectual dependency; speech style; social skills; linguistic diversity; digital technologies; education; interpersonal communication; standardization